Efficient ultrasonic signal processing techniques for aided medical diagnostics - Galluzzo, Francesca <1985> (Alma Mater Studiorum - Università di Bologna, 2013)
Ultrasound imaging is widely used in medical diagnostics as it is the fastest, least invasive, and least expensive imaging modality. However, ultrasound images are intrinsically difficult to be interpreted. In this scenario, Computer Aided Detection (CAD) systems can be used to support physicians during diagnosis providing them a second opinion. This thesis discusses efficient ultrasound processing techniques for computer aided medical diagnostics, focusing on two major topics: (i) Ultrasound Tissue Characterization (UTC), aimed at characterizing and differentiating between healthy and diseased tissue; (ii) Ultrasound Image Segmentation (UIS), aimed at detecting the boundaries of anatomical structures to automatically measure organ dimensions and compute clinically relevant functional indices. Research on UTC produced a CAD tool for Prostate Cancer detection to improve the biopsy protocol. In particular, this thesis contributes with: (i) the development of a robust classification system; (ii) the exploitation of parallel computing on GPU for real-time performance; (iii) the introduction of both an innovative Semi-Supervised Learning algorithm and a novel supervised/semi-supervised learning scheme for CAD system training that improve system performance reducing data collection effort and avoiding collected data wasting. The tool provides physicians a risk map highlighting suspect tissue areas, allowing them to perform a lesion-directed biopsy. Clinical validation demonstrated the system validity as a diagnostic support tool and its effectiveness at reducing the number of biopsy cores requested for an accurate diagnosis. For UIS the research developed a heart disease diagnostic tool based on Real-Time 3D Echocardiography. Thesis contributions to this application are: (i) the development of an automated GPU based level-set segmentation framework for 3D images; (ii) the application of this framework to the myocardium segmentation. Experimental results showed the high efficiency and flexibility of the proposed framework. Its effectiveness as a tool for quantitative analysis of 3D cardiac morphology and function was demonstrated through clinical validation. === L’ecografia è una tecnica diagnostica per immagini utilizzata nella pratica clinica, non invasiva, poco costosa e in tempo reale. La bassa qualità delle immagini rende l’interpretazione complessa e soggettiva. Per supportare i medici nella diagnosi è possibile utilizzare sistemi Computer Aided Detection (CAD). La tesi discute tecniche efficienti di elaborazione dei segnali ultrasonici per diagnostica medica supportata da computer. Vengono trattate due tematiche: (i) la caratterizzazione tissutale basata su ultrasuoni, finalizzata al miglioramento del protocollo bioptico per la diagnosi del tumore alla prostata; (ii) la segmentazione di immagini ecocardiografiche, finalizzata all’individuazione dei contorni delle strutture cardiache per misurare in modo automatico le dimensioni dell’organo e calcolare indici di funzionalità clinicamente rilevanti.